IJCM_11A: Clinico-epidemiological profile of malignancies in the tertiary care centres in Mangalore - Gupta Kashvi; Mithra Prasanna; Unnikrishnan B; Rekha T; Kumar Nithin; Chaturvedi Abhinav; Shetty Siddhant; Shankar Ravi; Singh Richa; Ayesha (Wolters Kluwer Medknow Publications, 2024)
Background: The Hospital-based Cancer Registry (HBCR) part of the National Cancer Registry Programme provides the number of cancer cases attending the hospital in various disciplines and the exact type of cases classified, diagnosed and treated. This study was done to assess the socio-demographic, clinical profile, and trend of malignancy cases in the tertiary care centres of Mangalore. Methodology: This Record-based retrospective study was conducted in tertiary care hospitals affiliated with Kasturba Medical College, Mangalore and all the cases of malignancies admitted during the study period were included. The data were collected using a proforma and analyzed using SPSS version 25.0. The results were expressed as proportions using appropriate tables and graphs. Results: A total of 600 cancer cases were identified, with females comprising nearly half 48.8%(n=293) and among them the highest number of cases, 28% (n=82) were found in the age group 60 and above. Overall, cancer cases appear to be more prevalent in older age groups for both genders. Among males, the most common cancers were Oral cavity cancers 34.2%(n=105), followed by Gastrointestinal (GI) tract cancers,16.3%(n=50). In females the most common cancers were found to be of the breast followed by uterine cancer then by oral cavity Conclusion: The prevalence of cancer in both genders were found to be almost the same. The highest number of cases were reported from Karnataka followed by Kerala. The highest prevalence was found in higher extremes of age above 60 years.